Protective Effects of Glochidion wallichianum Mull. Arg. on Ethanol-induced Liver Injury in Rats - Samuhasaneeto, Suchittra; Punsawad, Chuchard; Chaniad, Prapaporn (Trends in Sciences, 2022)
Chronic ethanol consumption leads to the development of liver disease. In the present study, the effects of Glochidion wallichianum Mull. Arg. ethanol extract (GWE) on chronic ethanol-induced liver injury in rats were evaluated. Total phenolic and flavonoid contents and in vitro antioxidant activities were determined. In the in vivo experiment, male Wistar rats were divided into 5 groups: Control, ethanol, ethanol plus low and high doses of GWE (ethanol+GWE300 and ethanol+GWE600, respectively) and GWE alone (GWE600). All treatments were administered orally for 28 days. Serum biochemical profiles, hepatic malondialdehyde (MDA) levels, antioxidant enzyme activities, cytochrome P450 2E1 (CYP2E1) expression, and liver histopathology were assessed. GWE contained high concentrations of total phenols and total flavonoids and exhibited inhibition of 2,2-diphenyl-1-picrylhydrazyl free radical. The GWE treatment significantly decreased alanine aminotransferase (ALT) levels, reduced hepatic MDA levels, increased catalase (CAT) activity, and improved histopathological alterations. However, compared with the control condition, GWE alone induced a low level of necrosis. The expression of the CYP2E1 mRNA was not different among the groups (p > 0.05). Based on these findings, GWE exerts a protective effect on ethanol-induced liver injury in rats through its antioxidant activity. HIGHLIGHTS Chronic alcohol abuse causes liver injury which leads to alcohol liver disease Administration of Glochidion wallichianum Mull. Arg. ethanol extract declined oxidative stress marker in hepatic tissue, improved hepatic antioxidant enzyme on chronic ethanol-induced liver injury in rats Glochidion wallichianum Mull. Arg. possibly serves as supplement to attenuate ethanol-induced liver injury GRAPHICAL ABSTRACT